REGENERASI PETANI: DAMPAK AGEING FARMERS DAN MODAL MANUSIA TERHADAP PRODUKTIVITAS PADI DI INDONESIA - Zata Hasyyati (Jurnal Ekonomi Pertanian Unimal, 2025)
The Indonesian agricultural sector faces structural challenges in the form of a regeneration crisis and an aging farming workforce (aging farmers). This study aims to analyze the impact of aging farmers and human capital quality (High School/Equivalent education) on rice productivity in Indonesia during the 2013-2024 period. By employing dynamic regression analysis through First Difference (FD) transformation and the inclusion of a lagged dependent variable, this study seeks to mitigate the risk of spurious regression in time series data. The estimation results indicate that the aging farmers phenomenon has a significant negative impact on rice productivity at the 10% significance level, with a coefficient of -2.58. Conversely, the human capital variable (High School+ education) does not show a statistically significant effect, indicating a skill mismatch phenomenon in rural areas. The model has passed all classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation. These findings provide important implications for policymakers: efforts to increase national food productivity cannot rely solely on physical inputs and formal education but must target youth farmer regeneration programs accompanied by specific and adaptive agricultural vocational training for modern technology.